Il volgarizzamento veneto della «Vita rhytmica Mariae atque Salvatoris» secondo il ms. Oxford, Bodleian Library, Canon. It. 280 (Carte Romanze, 2023)
Edition with critical notes and iconographic commentary on the Venetian vulgarization of Vita rhytmica Mariae transmitted by the ms. Canon. It. 280 of the Bodleian Library of Oxford. The vulgar work is the translation of a Latin poetic text, one of the most interesting examples of apocryphal matter.